Wheat particle size, insoluble fibre sources and whole wheat feeding influence gizzard musculature and nutrient utilisation to different extents in broiler chickens. Issue 1 (8th November 2018) - Abdollahi, Mohammad Reza; Zaefarian, Faegheh; Hunt, Hayley; Anwar, Muhammad Naveed; Thomas, David G.; Ravindran, Velmurugu
Abstract: A 21‐day experiment was conducted to investigate the effects of wheat particle size, insoluble fibre source and whole wheat (WW) inclusion on the gizzard musculature, intestinal architecture and nutrient utilisation of broiler chickens. The following seven treatments, all in mash form, were tested: control diet using finely ground wheat (Fine); control diet using medium‐ground wheat (Medium); control diet using coarsely ground wheat (Coarse); fine diet diluted with 10 g/kg lignocellulose (LC); fine diet diluted with 30 g/kg oat hulls (OH); fine diet diluted with 30 g/kg wood shavings (WS); and ground wheat in the fine diet replaced with 50 and 100 g/kg WW during the second (day 8–14) and third (day 15–21) weeks of the study respectively. Except for the LC diet, all treatments increased ( p < 0.05) the thickness of the caudodorsal thick muscle of gizzard compared to the fine diet. The highest ( p < 0.05) caudoventral thin and cranioventral thick muscle diameters in the gizzard walls were achieved with the OH and WS diets. Feeding OH, WS and WW diets improved ( p < 0.05) starch digestibility compared with the fine diet, while medium, coarse and LC diets had no effect ( p > 0.05). All diets containing fibre sources (LC, OH and WS) reduced ( p < 0.05) the energy digestibility compared to the fine diet. Birds fed OH and WS diets gained the lowest ( p < 0.05) weights. Feeding LC, OH, WS and WW diets increased ( p < 0.05) the feed per gain compared with the fine diet. The current results suggest that there is a potential for coarse particles, insoluble fibre sources and WW feeding to improve the gizzard musculature and digestibility of some nutrients, with the effect being more pronounced with the inclusion of structural fibre sources.